(untitled) (American Journal of Technology and Applied Sciences, 2023)
In the article, the speed of heat agent and local resistance coefficients in the process of heat exchange in a drum dryer for drying mineral fertilizers were experimentally studied, and an experimental research program was carried out in order to determine the parameters determining the high intensity of heat exchange.